Fully self-healable, highly stretchable, and anti-freezing supramolecular gels for energy-harvesting triboelectric nanogenerator and self-powered wearable electronics. (December 2021) - Khan, Amir; Ginnaram, Sreekanth; Wu, Chia-Hua; Lu, Hong-Wei; Pu, Yi-Fang; Wu, Judy I.; Gupta, Dipti; Lai, Ying-Chih; Lin, Hong-Cheu
Abstract: Deformable energy-harvesting devices that are self-repairable and possess broad working temperatures remain a challenge for autonomous flexible electronics. Herein, the self-healable, stretchable, and anti-freezing entirely gel-based triboelectric nanogenerator (TENG) with a wide working temperature range from − 40 to 80 °C is reported in this study. Initially, an electrode gel was prepared by mixing poly(lipoic acid) with supramolecular crosslinkers of Fe 3+ and phytic acid (PA), and the conductive polymer poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) was added. Secondly, a triboelectric gel was synthesized using amino- and hydroxy-terminated poly(dimethylsiloxane) (PDMS) along with isophorone diisocyanate and silicone oil. These gel networks were constructed by supramolecular interactions of reversible physical bonds and able to contribute high stretchability up to 50 times strain with fast self-healability (4 min for electrode gel and 24 h for tribolayer gel). The resulting gel-based TENG maintained excellent performance even after 5000 cyclic operations and showed stable performance after multiple cut/self-healing processes. Its outputs were increased as it was biaxially stretched up to 150% strain to retain its elasticity, ensuring its applicability in flexible uses. Moreover, the energy-harvesting capability was verified to be applicable from − 40 to 80 °C. Last, the gathered energy from the gel-based TENG was demonstrated to power up commercial electronics. Graphical Abstract: An entirely gel-based triboelectric nanogenerator (TENG) featuring self-healable, stretchable, and anti-freezing properties is presented. The device outputs are explored by cut/self-healing processes of three complete layers, biaxial stretching along with anti-freezing performances in a wide temperature range of − 40 to 80 °C. This gel-based TENG can serve as a power source for electronic devices (e.g., watch and calculator). ga1 Highlights: An entirely gel-based TENG with a wide working temperature range from − 40 to 80 °C is reported. An electrode gel was prepared by mixing poly(lipoic acid) with supramolecular crosslinkers of Fe 3+, PA, and PEDOT:PSS. A triboelectric gel was synthesized using amino- and hydroxy-terminated PDMS along with IPDI and silicone oil. The resulting gel-based TENG maintained excellent performance even after multiple cut/self-healing processes. Its outputs were increased as it was biaxially stretched up to 150% strain, ensuring its applicability in flexible uses.